Links Between Beliefs and Cognitive Flexibility
VIII, 213 p.
Keywords: With the world and its structures becoming ever more complex, and the nature of future employment becoming ever more unpredictable, the notion of ‘cognitive flexibility’ has a high profile in educational and psychological debate. The contributions in this volume analyze the nature of cognitive flexibility, as well as the impact of different types of beliefs on cognitive flexibility. Making adequate decisions requires considering input from a variety of continuously evolving sources rather than adhering to predetermined procedures. Adopting a position in a debate necessitates the critical evaluation of different alternatives, while solving a problem entails selecting appropriate problem-solving strategies. Meanwhile, studying requires students to integrate a range of interventions, and treating a patient involves making a differential diagnosis. The common factor, cognitive flexibility, lies at the core of effective functioning in complex, domain-specific environments. Cognitive flexibility can be described as the disposition to consider diverse information elements while deciding on how to solve a problem or to execute a learning-related task in a variety of domains. The concept of ‘disposition’ implies that individuals will not always demonstrate cognitive flexibility even if they are in principle able to act in a cognitively flexible way. The notion does not require that alternatives are always deliberately considered, which is why this volume’s tandem discussion of beliefs is key element of the discussion. Beliefs play a central role in cognitive flexibility and relate to what individuals consider to be important, valid and/or true. Of specific interest is the relationship between epistemological beliefs and cognitive flexibility, especially as a particular subset of epistemological beliefs seems to be a prerequisite to a cognitively flexible disposition.